ANALISIS TERHADAP KEMAMPUAN GURU BAHASA ARAB DALAM PENGEMBANGAN KURIKULUM TINGKAT SATUAN PENDIDIKAN DI MADRASAH PKPPS SWASTA IST’DADUL MU’ALLIMIEN KECAMATAN PENGABUAN PROVINSI JAMBI TAHUN PELAJARAN 2032/2024 - ABDURRAHMAN, (UNISAN JURNAL, 2024)
The presence of Arabic in public schools, especially Madrasah Aliyah, has experienced quite significant development since the implementation of the Education Unit Level Curriculum (KTSP) in 2006. It is possible to teach Arabic at Madrasah Aliyah in all classes and departments as an optional foreign language subject. Arabic is a subject that is not only popular as a compulsory subject in madrasas and Islamic boarding schools. Therefore, developing an Arabic language curriculum as an optional foreign language subject is very urgent.This research aims to determine the development of the Arabic language curriculum as a foreign language subject at the Isti'dadul Mu'allimien Private Madrasah Aliyah. The approach used is a qualitative descriptive approach with a case study type of research. Technique The data collection is observation, in-depth interviews, and documentation. The data analysis used in this research is descriptive analysis with a process of data reduction, data presentation and data verification. The results of this research show: (1) The characteristics of the development of the Arabic language curriculum as a foreign language at the Isti'dadul Mu'allimien Private Madrasah Aliyah are found in the basic development and principles, as well as the development of the curriculum elements. Curriculum development at the Isti'dadul Mu'allimien Private Madrasah Aliyah consists of developing all its elements. As for the content elements, there is no development and it is still the same as the national curriculum. (2) Obstacles in developing the Arabic language curriculum as a foreign language at the Isti'dadul Mu'allimien Private Madrasah Aliyah, namely: lack of coordination of curriculum developers, lack of Arabic teachers, Arabic being a less prioritized subject, uneven student abilities , the presence of non-Muslim students. The solutions taken include: providing motivation and enthusiasm to learn Arabic, strict material selection, using fun methods, organizing Arabic Reading and Writing (BTA) activities outside the classroom with a mentoring system and providing motivation about the usefulness of the Arabic language. Keywords: Curriculum Development, Arabic, Foreign Language Subjects